Kinetics and prediction of HBsAg loss during therapy with analogues in patients affected by chronic hepatitis B HBeAg negative and genotype D. (14th January 2013) - Boglione, Lucio; D'Avolio, Antonio; Cariti, Giuseppe; Gregori, Gabriella; Burdino, Elisa; Baietto, Lorena; Cusato, Jessica; Ghisetti, Valeria; De Rosa, Francesco G.; Di Perri, Giovanni
Abstract Background & Aims In patients affected by chronic hepatitis because of HBV infection, long‐term suppressive therapy with nucleos(t)ides analogues in the HBeAg− patients has shown low effects on HBsAg titre (qHBsAg) decrease, and HBsAg loss is difficult to achieve. Thus, in this type of patients the main goals of antiviral therapy is the suppression of HBV‐DNA and ALT normalization. Methods We retrospectively evaluated different qHBsAg kinetics in 134 treatment‐naïve patients having the same characteristics: HBeAg‐, infection sustained by HBV genotype D and persistently undetectable HBV‐DNA. Patients were treated with NAs therapy (lamivudine, adefovir, telbivudine, entecavir and tenofovir) for at least 2 years. qHBsAg was performed every 6 months. Results Our results showed a significantly greater qHBsAg decline after 2 years in patients treated with tenofovir (0.45 logIU/ml) than in patients treated with telbivudine (0.12 logIU/ml; P < 0.001). The calculated expected time to HBsAg loss was shorter in the tenofovir group than in the telbivudine group (nearly 17 vs 63 years, P < 0.001). Conclusions HBeAg negative patients infected by HBV genotype D should be treated with more potent NAs such as entecavir or tenofovir to obtain a significant qHBsAg decrease, but the achievement of HBsAg loss seems to require almost two decades of therapy.